The Understanding of Meaning and Cultural Significance of Leisure, Recreation and Sport in Malaysia towards Capitalizing Human Resources - Aman, Mohd Salleh; Omar Fauzee, Mohd Sofian; Mohamed, Mawarni (2007)
This paper is concerned with examining the impact towards capitalizing human resource (i) the meaning of leisure, recreation and sport in the context of Malay language and (ii) the cultural significance of leisure, recreation and sport in Malaysia. There is no single word in Malay that could be translated as leisure and recreation. Most Malaysians understand leisure as “kegiatan masa lapang” (free time activity) or “waktu senggang” and recreation as” riadah” (active recreation) or “santai” (passive recreation). The direct translation for sport is “sukan”. The availability of the term” sukan” has helped sport to be more familiar among Malaysians than leisure and recreation. Leisure, recreation and sport in Malaysia are manifested in the patterns of the Malay language and culture. Culture is commonly used to describe a way of life. The symbols and rituals of some Malaysians indicate the strength of their adherence to certain behavioural norms related to good health and well-being. Attitude wise, Malaysians seem to enjoy „time after work‟, holidays and out of door activities during their leisure time. In Malaysia, sport persons are not as popular as a hero / role model as compared to a politician. Furthermore, Malaysians, being Eastern-oriented, are more inclined to incorporate their religious values into leisure, recreation and sport, although Islam allows one to proceed towards excellence in sport but the emphasis is on healthy bodies, family recreation and social harmony. Since sport is generally based on Western interpretations, many regulations such as dress codes, do not in accordance to Islamic principles, and this may make it difficult for some Malaysians, especially Muslim women, to participate.